Pengembangan Media Pembelajaran Hand Out Tipe Corner Pada Mata Pelajaran Biologi SMP Kelas VIII Pada Materi Sistem Pencernaan - Fauziati Fauziati; Asmawati Kamal; Afrahamiryano Afrahamiryano (Eduscience Development Journal, 2019)
This research was motivated because the media in schools did not facilitate students in learning. The purpose of this research is to produce valid and practical hand outs. This type of research is development research (Research and Development), using 4D development, namely difine, design, development, and dissemination. The instruments used were questionnaires for material experts, language experts, response teachers, and student responses. The subjects of the trial in this study were 22 eighth grade students of Bukit Sundi 1 Public Middle School, but in this study the distribution was not carried out. In the defining stage, needs analysis, student analysis and task analysis were carried out, in the design of the design media design was carried out, at the development stage validation tests were carried out by 3 validators and practical tests by teachers and students at Bukit Sundi 1 Junior High School class VIIIe. Based on data analysis, questionnaire and language expert validation reached 85.30% and 85.50%. Practicality by teachers reached 88.14% and 87.00% students. Based on these stages, it is produced a valid and practical Corner type learning media